2013
DOI: 10.2188/jea.je20120221
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Diabetes Self-Reports in the Saku Diabetes Study

Abstract: BackgroundDiabetes is an important risk factor for cardiovascular disease, certain types of cancer, and death, and self-reports are one of the most convenient methods for ascertaining diabetes status. We evaluated the validity of diabetes self-reports among Japanese who participated in a health checkup.MethodsSelf-reported diabetes was cross-sectionally compared with confirmed diabetes among 2535 participants aged 28 to 85 years in the Saku cohort study. Confirmed diabetes was defined as the presence of at lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
42
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 24 publications
4
42
0
3
Order By: Relevance
“…A self-reported questionnaire always involves misclassification. However, one past study 16 demonstrated high specificity of self-reported diabetes in a similar setting in Japan. This suggests that, although a self-reported questionnaire is not perfect, participants with self-reported diabetes were likely to have true diabetes.…”
Section: Discussionmentioning
confidence: 93%
“…A self-reported questionnaire always involves misclassification. However, one past study 16 demonstrated high specificity of self-reported diabetes in a similar setting in Japan. This suggests that, although a self-reported questionnaire is not perfect, participants with self-reported diabetes were likely to have true diabetes.…”
Section: Discussionmentioning
confidence: 93%
“…Em pesquisa realizada no Japão, com indivíduos de 28 a 75 anos, observou-se sensibilidade de 70,4%, especificidade de 97,3%, VPP de 75,7% e VPN de 96,5% para o relato de DM. Esse resultado considerou que a morbidade referida pode ser utilizada como fonte de informação para estudos epidemiológicos relacionados ao DM, principalmente, quando não houver possibilidade de utilização de marcador bioquímico 23 É preciso considerar que as informações relatadas são passíveis de erros em virtude de sua dependência do acesso aos serviços de saúde, da realização de procedimentos diagnósticos 24 , da capacidade do indivíduo de recordar as informações, assim como do desejo de informá-la 25 . Por isso, validar as informações referidas é fundamental para aumentar a confiabilidade da morbidade referida, tendo em vista que erros na determinação da prevalência da doença podem influenciar a qualidade da informação e, por consequência, os planos de ação das políticas públicas de saúde 16 .…”
Section: Discussionunclassified
“…Neste Este estudo observou elevadas prevalências de especificidade do relato do DM entre os idosos. Condição semelhante foi encontrada por outras pesquisas que verificaram a não existência de níveis glicêmicos alterados entre aqueles que referiram não terem sido diagnosticados com a doença 5,23,26,27 .…”
Section: Discussionunclassified
“…In international studies that have investigated self-reported DM among adolescents, adults and older adults, the sensitivity ranged from 30.1% (95%CI 24.0–36.2) to 70.4% (95%CI 64.5–75.8) 5,9,13,20 . The results show that, as in this study, sensitivity depends on the study population.…”
Section: Discussionmentioning
confidence: 99%